Evaluation of the effect of different surface treatments on the retention of posts: A laboratory study - Prithviraj D; Soni Romesh; Ramaswamy Sushma; Shruthi D (Wolters Kluwer Medknow Publications, 2010)
Background and Objectives : There are numerous post and core systems variety of materials. Several methods are used to increase the retentive strength.The present study was conducted with the purpose of analysis of the effect of surface treatment with ethyl alcohol, resin primer and air-borne alumina particle abrasion on retention of glass fiber posts, carbon fiber posts and cast metal posts Materials and Methods : Surface treatment of glass fiber posts, carbon fiber posts and cast metal posts was done with ethyl alcohol, resin primer and air-borne alumina particle abrasion and cemented with dual cure resin cement into the post spaces prepared in the teeth. For the Retentive force test, a screw driven universal testing machine was used to apply tensile load to the post. The force required to dislodge each post from prepared post space was recorded. Statistical Analysis : Comparison of the mean retentive strength was done using two-way Analysis of Variance (ANOVA) followed by Bonferroni method for multiple comparisons. Results : Significant difference in the retentive strength between air borne alumina particle abrasion and resin primer treated posts was (P < 0.001) noticed. Further, there was no significant difference between ethyl alcohol and resin primer treated posts Conclusion : Air-borne alumina particle abrasion increased the retentive strength of all the type of posts used in this study. Treating the surface of the posts with resin-primer and ethyl alcohol produced no statistically significant difference in the retentive strength.